(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the morphological characteristics of fetuses diagnosed with congenital diaphragmatic hernia (CDH) and to evaluate pregnancy and neonatal outcomes. Methods: A retrospective descriptive study was conducted on 138 pregnant women carrying fetuses diagnosed with CDH by prenatal ultrasound at Hanoi Obstetrics and Gynecology Hospital from January 2020 to August 2025. Results: Most cases of CDH were left-sided (89.1%). Right-sided hernias accounted for a smaller proportion (10.1%), and only one case was recorded as a central defect (0.8%). Herniated organs most frequently involved multiple viscera (34.8%), with the stomach and intestines being the most common components (83.3% and 65.2%, respectively). Right-sided CDH was associated with a higher mortality rate (50.0%) compared with left-sided CDH (14.9%) (p = 0.021). The presence of liver herniation was also associated with significantly higher postoperative mortality (55.6%) than in cases without liver herniation (5.1%). After birth, all neonates required endotracheal intubation (100%); 80.5% received conventional mechanical ventilation, 19.5% received high-frequency ventilation, and 28.5% required vasopressor support. Surgical repair was performed in 90.5% of cases, predominantly with primary diaphragmatic closure. The postoperative mortality rate was 18.1%. Conclusion: The study showed that most cases of congenital diaphragmatic hernia (CDH) were detected at 22–28 weeks of gestation, predominantly left-sided, and occurred in mothers with normal health and obstetric histories. Right-sided CDH, especially when accompanied by liver herniation, was associated with poorer prognosis and higher mortality. Most pregnancies were continued, and all newborns required intensive resuscitation and surgical repair, mainly primary diaphragmatic closure. Postoperative outcomes were favorable, with survival rates exceeding mortality